Study of the Utilization of Carbon Electrodes to Reduce Dissolved Ions from Coal Stockpile Wastewater - Andi Arif Setiawan; Reno Fitriyanti (Program Pascasarjana Universitas Sriwijaya, 2021)
The advancement of science and technology plays a very important role in encouraging industrial progress. In addition to having a positive impact on the economy, industrial progress, on the other hand, has a negative impact in the form of pollution. One of the industrial activities is the coal mining industry. Various ways to deal with pollution include the electrolysis method, in which the liquid waste is flowed by a direct electric current through the electrode media. The purpose of this study was to examine the length of electrolysis and the amount of electric current used to reduce dissolved ions and total dissolved solids from coal stockpile wastewater. The method used is a survey in the form of sampling followed by waste treatment using electrolysis. The results showed that the combination of electrolysis time of 120 minutes and electric current of 3 A showed that the highest dissolved ions decreased by an average of 1,692.3 µs / cm from the initial pre-treatment of 1772 µs / cm. The highest mean decrease in total dissolved solids was 660.67 ppm from the beginning before treatment of 909 ppm.